Protocol for a mixed-methods feasibility study for the surviving opioid overdose with naloxone education and resuscitation (SOONER) randomised control trial - Peter Jüni; Carol Strike; Rita Shahin; Kevin Thorpe; Douglas Campbell; Aaron Orkin; Shaun Hopkins; Michelle Klaiman; Janet A Parsons; Kate Sellen; Geoffrey Milos; Amy Wright; et al. (BMJ Open)
Introduction The surviving opioid overdose with naloxone education and resuscitation (SOONER) project uses co-design and trial methods to develop and evaluate a point-of-care overdose education and naloxone distribution (OEND) tool. We plan to conduct a randomised controlled trial to assess the effectiveness of our OEND tool in comparison with best available standard of care by observing participants’ performance as a responder to a simulated overdose. Recruiting and retaining people at risk of or likely to witness opioid overdose raises scientific, logistical and bioethical challenges. A feasibility study is needed to establish the effectiveness of recruitment and retention strategies and acceptability of study procedures prior to launching the full trial.Methods and analysis Strategies to enhance recruitment include candidate-driven recruitment, verbal informed consent, and attractive, destigmatising materials. Adults at risk of or likely to witness opioid overdose will be recruited through an urban emergency department, inpatient and ambulatory addiction medicine service, and outpatient family practice settings. Participants randomised to the intervention arm will receive our OEND intervention; those in the control arm will be referred to existing OEND programme. Retention procedures include participant reminders, flexible scheduling, cash and comfort compensation, and strategies to maintain a consistent relationship between individual study staff and participants. Within 2 weeks following recruitment, participants will engage as a responder to a manikin-simulated overdose, and complete overdose knowledge and attitudes questionnaires. The primary outcome is recruitment and retention feasibility, defined as the recruitment of 28 participants within 28 days of recruitment and <50% attrition at the overdose simulation. Staff and participant feedback will also be collected and considered.Ethics and dissemination The study has been reviewed by ethics boards at St. Michael’s Hospital, Toronto Public Health and the University of Toronto. Dissemination will occur through peer-reviewed publication and presentations.Trial registration number ClinicalTrials.gov registry (NCT03821649).